From Childhood System Contact to Adult Criminal Conviction: Investigating Intersectional Inequalities using Queensland Administrative Data - Matthews, Ben (Journal of developmental and life-course criminology, 2022)
It is well known that youth justice contact is associated with criminal conviction in adulthood. What is less well understood is whether ‘cross-over’ children, who have contact with both child welfare and youth justice systems, experience relatively worse outcomes and, if so, whether these outcomes vary by important demographic factors, such as sex and race. Criminal careers scholars have examined patterns of adult convictions for different groups, but attempts to understand intersectional variation in these outcomes have been constrained by limitations of standard statistical analysis. Using administrative data from the Queensland Cross-sector Research Collaboration, we adopt a flexible regression model specification to explore the cumulative effects of both child welfare and youth justice contact on adult conviction trajectories, and how these associations vary by sex and Indigenous status. We find clear evidence across all demographic groups that contact with both justice and welfare systems in childhood is associated with increased likelihood and severity of conviction trajectories in adulthood. The cumulative effect of cross-over status results in greater equity of negative outcomes across groups, although the conviction profile is worst for Indigenous men. Evidence of an additional inequality is present only for non-Indigenous women, who have the lowest likelihood of conviction overall. We conclude that while cross-over children are at elevated risk of conviction in adulthood, the nature and seriousness of their conviction pathways is conditional on pre-existing intersectional inequalities. The model specification used is a promising method by which to explore the existence of such inequalities.